SOSIALISASI EFEKTIVITAS PEMILU DALAM MEMBERIKAN PEMAHAMAN POLITIK GUNA MENINGKATKAN KESADARAN BERPOLITIK MASYARAKAT - Bima Pratama; Danang Wijaya Saputra; Elvika Permata Sari; Fitta Verolina Sinaga; Indra Syahputra Siahaan; Jumriani Jumriani; Linda Safitri; M. Supra Setyo; Putri Geovani Mayori; Sri Andini (Bajang Institute, 2022)
The purpose of this journal is to provide broader knowledge related to the effectiveness of elections in providing political understanding in order to increase political awareness of the Kukerta student community at the University of Riau consistently trying to increasing community participation, especially Kuala Lemang Village, Keritang Subdistrict, Indragiri Regency downstream for the prevention of abstentions. the activities carried out by Kukerta students at the University of Riau and the village head of Kuala Lemang were to socialize the election to the people who were present, explain in detail the importance of elections in social life after which students also made videos which were uploaded to YouTube related to election socialization.